Forecasting the Future of Futsal Performance: Integrating Artificial Intelligence, Cognitive Factors, and Environmental Constraints - Gharavi, Seyed Erfan; Shaabani Ezdini, Ebrahim; Sahar Beik (Journal of Foresight and Health Governance, 2026)
This review aimed to forecast the future of futsal performance by integrating evidence from artificial intelligence (AI), cognitive science, and ecological dynamics. Futsal is a high-intensity, time-constrained sport characterized by rapid transitions, frequent ball contacts, and continuous perception–action coupling. A narrative review approach was adopted to synthesize peer-reviewed studies relevant to performance analysis, decision-making, tactical behavior, and technology-enhanced training. The literature indicates that AI-driven tools, including machine learning models, tracking systems, and wearable technologies, are increasingly used to monitor player behavior, optimize workloads, and support tactical analysis. At the same time, cognitive factors such as executive functions, anticipation, attention, and perceptual-cognitive expertise play a central role in successful performance in team sports, particularly in fast and information-rich environments such as futsal. Environmental constraints, including space, rules, number of players, and task design, further shape behavior through adaptive interactions between the athlete and the game context. Taken together, these domains suggest that futsal performance should be conceptualized as a dynamic, multidimensional system rather than as an outcome of isolated physical or technical qualities. The review proposes that the future of futsal performance will depend on the integration of intelligent technologies, high-level cognitive functioning, and ecologically valid training environments.